Disparidades regionais e estrutura produtiva da agricultura brasileira: Uma análise espacial e setorial 2013-2017 e 2018-2022 - Luís Abel da Silva Filho; Bruno de Oliveira Cruz; Juliana Aguiar de Melo; Luiz Carlos de Santana Ribeiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– Brazilian agriculture, despite notable growth in recent years and having been responsible for a significant portion of trade surpluses, presents strong spatial heterogeneity. This paper analyzes Brazilian agriculture spatially and structurally, differentiating between permanent and temporary crops Local Indicators of Spatial Association is used to identify the spatial association between credit, area, production value and labor force. This exploratory analysis then assists in a structural analysis for Brazilian macroregions, with the objective of identifying how each region responds to investment shocks in terms of impact on GDP, spillovers and effects on regional inequality. The main results show that there is a spatial association between the variables analyzed, with a greater association between area, credit and output for temporary crops, compared to permanent crops. Furthermore, there are differences in the responses to shocks in each region. Investment in agriculture in the North, Northeast and Mid-West regions would contribute to reducing regional inequalities, while in the South and Southeast, it would increase.
Keywords: C67; Q10; R15; 330; spatial analysis; Brazilian agriculture; permanent farming; temporary farming; input-output